Pengukuran Kinerja Perusahaan Dengan Menggunakan Metode RGEC - Adi Sari, Inayah Adi; Riyanto, Riyanto; Hastuti, Novika Wahyu; Nugraha, Aryan Eka Prastya (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2025)
This study aims to test the performance enterprises in the banking sector in the era of the pasca Covid-19 pandemic. Measuring the bank's financial performance using the RGEC method, namely by looking at the NPL (Non Performing Loan), Good Corporate Governance (GCG), Return on Asset (ROA) and Capital Adequacy Ratio (CAR) ratios. The population in this study is banking companies listed on the Indonesia Stock Exchange. Sampling using the purposive sampling method, namely banking companies listed on the Indonesia Stock Exchange in 2021-2023, complete audited financial statements are available. The sample in this study amounted to 39 financial statements. The data analysis technique in this study uses multiple linear regression analysis. The results of this study concluded that the NPL and ROA variables had a negative and significant effect on PBV, while the GCG and CAR variables had a positive and significant effect on PBV. The results of this study are expected to provide benefits for stakeholders in making decisions to invest, especially in banking companies. Key word: Capital Adequaty Ratio (CAR); Good Corporate Governance (GCG); Non Performing Loan (NPL); Return on Asset (ROA); ); Price to Book Value (PBV)